An Evaluation Of Postgraduate School-Based Teacher Education Program In Malaysia - Tan, Cheng Im (2011)

(untitled)
PHD 2011 The primary purpose of this study was to evaluate the strengths and weaknesses of the postgraduate SBTE program as an alternative route in training teachers. The post graduate SBTE was conducted by using modules through self-directed learning and tutorials, with the collaboration of the school mentor teachers. Tujuan utama kajian ini adalah untuk menilai kekuatan dan kelemahan program LPBS lepas ijazah sebagai satu kaedah alternatif dalam melatih guru. Program LPBS lepas ijazah dilaksanakan dengan menggunakan modul-modul melalui pembelajaran arah kendiri dan tutorial, dengan kolaborasi guru pembimbing di sekolah.